مقارنة بعض طرائق التعويض الأحادي للبيانات المفقودة لدالة الكثافة الاحتمالية للتوزيع الطبيعي ثنائي المتغيرات - عباس, تهاني مهدي; محمد, محمد جاسم; نايف, قتيبة نبيل (Journal of Economics and Administrative Sciences, 2010)
In this paper we suggest new method to estimate the missing data  in bivariate normal distribution and compare it with Single Imputation  method (Unconditional mean and Conditional mean) by using simulation.